Sur la convergence et l’ultraconvergence de l’intégrale du type Laplace—Stiltjes - Miškelevičius, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Мишкялявичюс. О сходимости и сверхсходимости одного интеграла типа Лапласа — Стильтьеса A. Miškelevičius. Vieno Laplaso—Stiltieso tipo integralo konvergavimo ir virškonvergavimo klausimu